A Study of Biostratigraphy of Sinjar Formation in selected sections from northern Iraq - Al-Dulaimi, Esraa Khalifa; Al-Dulaimi, Salam Ismeal (Iraqi Journal of Science, 2022)
Late Paleocene –Early Eocene algae and benthic foraminifera were identifiedfrom the Sinjar Formation that crop out in three selected section from northernIraq. The selected sections: (Derbandikhan ,Qara dagh, Wara Mali has beenmeasured in the field and closely sampled to undertake details. A number of (131)samples were collected illustrating all the lithological changes along the sections,The limestone in the studied section is rich in algae and large benthic foraminifera,The investigation of the thin sections allowed us to identify the (47 ) species offoraminifera and (34) species of algae , Five biozones were distinguished for algaewhich are :a- Amphiroa iraquensis range zone ,b- Trinocladus perplexus range zone,c- Lithothamnium – Pagodaporella wetzeli –Lithoporella melobesides Assemblagezone ,d- Cymopolia kurdistanensis- parkerella Sp.- Dissocladella deserta - JaniaSp. Assemblage zone, e- Clypeina merienda –Distichoplax biserialis -Mesophyllum Sp,.-Archaeolithothamnium cf dollonii Assemblage zone. Fivebiozones were distinguished for large benthic foraminifera which are :- a-Cuvillierina sireli – Cuvillierina vallensis - Cibicides nammalensis – Rotaliatrochidiformis Assemblage zone ,b-Miscellane miscella –Discocylina variansAssemblage zone , c-Idalina sinjarica –Nummulites globulus –Spherogypsinaglobula –Somalina Sp.- Alveolina globosa Assemblage zone, d-Orbitolites Sp. -Assilina Sp.- Ovulites Sp.- Cribogoesella Sp, Assemblage zone, e-Opertorbitolitestransitorius range zone. The age of this formation is Late Paleocene-Early Eocenein the studied section.